The Effect of Bandwidth on Speech Intelligibility in Albanian Language by Using Multimedia Applications like Skype and Viber - Sabrije Osmanaj; Altin Shala; Blerta Prevalla (Institute of Advanced Engineering and Science, 2017)
This paper intends to analyze subjective measurements of intelligibility of speech on Albanian language during the conversation between two people using applications which today are very used for communication such as Skype and Viber. The measurement is done as follows: on the entry part of the transmission system sentences or words are spoken or just syllables while on receiving part is recorded what is heard; the percentage of words, sentences or syllables correctly received, on proportion to those imposed on the entry of the system, providing the percentage of intelligibility (the words, sentences or syllables). Methods of measurements are made at different speed of the Internet, in an environment without noise and with noise, in order to see the impact on understanding of the speech with different target parameters.